Mental health care delivery in poor settings through trained female community health workers: A five-year intervention program in Somaliland - Abdi, Yakoub Aden; Said, Nasir Ibrahim; Abdi Hared, Yusuf; Ayeh, Ismail; Walhad, Said Ahmed (Somali Health Action Journal, 2021)
Background: The situation of mental health globally is alarming particularly in developing countries. In Somaliland/Somalia, every third person may be suffering from some sort of mental illness according to the World Health Organization. Major barriers to improve mental health include stigma and lack of skilled human resources. Objectives: The aim was to explore the feasibility of organizing integrated community-based mental, epilepsy and mother and child health services delivered by trained female community health workers (FCHWs) in three urban sites (Borama, Baki and Dila) in the Awdal Region, Somaliland. Methods: After selection of the 3 project sites and recruitment and training of project staff, a baseline survey was carried out. First, the sites were properly mapped based on existing geographical administrative sectors and sub-sectors of the sites. Then a representative sample of 2,722 households was randomly selected from all the 3 sites. The female head of each of those households were then interviewed using a questionnaire containing 22 questions on the target groups. The questionnaire responses were coded, and data analysed using Statistical software program, SPSS. After the baseline survey, the FCHWs were deployed in the sites assigning a specified area to each female worker. The FCHWs worked 6 hours per day 6 days per week and were required to visit 6 families each day including follow-ups. Their activities included identification of patients with severe mental illness (SMI) or with epilepsy, counselling, distribution of medications, follow-up of patients already on medication, referral, stigma reduction and documentation of their daily activities in logbooks. Results: The baseline study showed that 12% of the households were taking care of at least one person with SMI each, while 7% had one person with epilepsy each. Of the patients with SMI, 18% were on chains. During the project period (2015-2019), the number of people with SMI or with epilepsy who benefited from the project was 2.225 and 738 respectively and their families empowered through increased mental health awareness. Among the patients with SMI, 237 were on chains before intervention and 85% of them were successfully released from their shackles. Conclusions: This project has shown that deployment of trained and supported FCHWs can be used to reduce the mental health care gap in Somaliland. It is suggested as a model project which could, hopefully, be replicated and tested in other similar settings.